2019
DOI: 10.5430/ijba.v10n2p82
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Programmes and Employees Retirement Preparedness: Empirical Evidence From the Educational Sector in Kenya

Abstract: Retirement is a process with employees planning decisions generally focusing on the subjective life expectancy, a mental model of years remaining before one dies. Indeed, the real exit of an individual from a career job is accompanied by changes that include social and psychological, resources leading to variations in an individual’s well-being. The purpose of this study was to assess how employees’ engagement in psychosocial programmes affects their retirement preparedness in the education sector in Kenya. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…In presenting a similar, psychosocial, financial and personal health programmes measures also exhibited mean score of less than 3 implying pre-retirees were indeterminate of extent of participation in activities related to separation planning. Despite the findings of other studies that psychosocial factors such as social embeddedness, are essential in retirement planning (Gathiira et al, 2019b;, the study findings paint a blurred image of retirement preparedness by pre-retiree teachers. In support of previous studies (Gathiira, Muathe & Kilika, 2018), the study portrayed that pre-retirees had not engaged in activities that provided financial literacy and investment to supplement salary income to an extent of majority not meeting recurrent expenditure in the absence of salary.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In presenting a similar, psychosocial, financial and personal health programmes measures also exhibited mean score of less than 3 implying pre-retirees were indeterminate of extent of participation in activities related to separation planning. Despite the findings of other studies that psychosocial factors such as social embeddedness, are essential in retirement planning (Gathiira et al, 2019b;, the study findings paint a blurred image of retirement preparedness by pre-retiree teachers. In support of previous studies (Gathiira, Muathe & Kilika, 2018), the study portrayed that pre-retirees had not engaged in activities that provided financial literacy and investment to supplement salary income to an extent of majority not meeting recurrent expenditure in the absence of salary.…”
Section: Discussioncontrasting
confidence: 99%
“…Pre-retirees' engagement in psychosocial programmes had an aggregate mean score of 3.05 and a standard deviation of 1.12 which suggested that pre-retiree teachers' participation in activities that foster mentorship opportunities, social orientation, and retirement counseling was indistinguishable. The findings concur with Gathiira et al (2019b) and Itika (2011) that, despite mentorship, coaching, community involvement and volunteer activities being essential in employee retirement planning, employees seldom participate as expected. Considering the empirical findings that psychosocial factors such as social embeddedness, are essential in retirement planning (Shultz & Henkens, 2010), the study findings raises a great concern on retirement preparedness.…”
Section: Summary Of Aggregate Mean Scores For the Variablessupporting
confidence: 88%
See 3 more Smart Citations